Ensino e aprendizagem de geografia: desafios em tempos de pandemia da Covid-19 no Colégio Estadual Cívico Militar Cândido Portinari em Ampére/PR - Zabot, Daniel Felipe (2023)
The present dissertation was elaborated from the analysis of the teaching and learning process of Geography during the Covid-19 pandemic at Colégio Estadual Cívico Militar Cândido Portinari, located in the municipality of Ampére, State of Paraná. It is considered the fact that the professional teacher, in the course of the pandemic crisis, was faced with new ways of teaching and learning, experiencing this moment on the school floor and perceiving the difficulties of the students. To this end, we seek to understand the Covid- 19 pandemic and its consequences for basic education in Brazil and Paraná, discussing the main theoretical and methodological guidelines that supported the teaching and learning process during the pandemic period (2020 and 2021), examining, especially, as the remote teaching adopted in Geography classes in the 9th years of the aforementioned teaching institution occurred. The research is justified by the need to understand whether the teaching and learning methodologies used in Geography classes, in the last grade of Elementary School, generated learning in the pandemic period. In this sense, we used works by several authors, in addition to the application of a questionnaire with questions about their conceptions of general learning and Geography in that historical period. Throughout the reflections promoted during this work, it was possible to perceive the innumerable challenges faced by the students for the learning to be effective, even if from different ways and in the face of different social and educational issue.